Optimization of doping process towards rutile-phased titanium dioxide nanorods array for ultraviolet photodetector applications - Mohammad Mokhtar, Salina (2023)
Titanium dioxide has gained attention in current fundamental research for photodetector application. Commercial UV photodetectors uses Si-based materials that have a low bandgap and needed a filter to filter-out visible light wavelengths. For that reason, TiO2 is widely studied as it has a wide bandgap that absorbs only UV wavelength. Even so, the slow carrier transport of TiO2 has been considered a drawback that can limit its full potential in these applications. Focusing on the electronic properties of the material, this study used several dopant concentrations to enhance rutile TiO2 electron concentration and mobility by using niobium (Nb) and boron (B) as dopants in nanorods TiO2. Well-aligned TiO2 nanorods were fabricated with 1.00 mL of TiO2 precursor as a preliminary study. Herein, the Nb and B-doped rutile TiO2 nanorods were fabricated by using hydrothermal method with FTO as a substrate. Based on the finding, doping process was successfully done with confirmation on the presence of Nb and B dopants in TiO2 lattice by XPS spectroscopy. Photocurrent analysis of the TiO2 nanorods shows increasing current approximately 2.3 times larger than undoped TiO2 for 0.25 w.t.% Nb doped, and 1.8 times larger for 1.00 w.t.% of B doped with bandgap of 3.09 and 3.04 eV, respectively. While B doping does not give significant changes to the nanorod, Nb dopant inhibits nucleation sites on the FTO thus reducing the density of nanorods in high doping concentration. Annealing treatment was done to enhance the crystallinity of the nanorods with the annealing temperature varied from 200 to 500 °C. Annealing treatment on both samples showed an increase in the photocurrent with enhancement on the crystallinity of samples at 300 °C annealing temperature. The results prove that electron concentration and mobility of rutile TiO2 nanorods can be enhanced by using Nb and B dopants. Highly crystalline nanorods can be achieved with annealing treatment at 300 °C that will further enhance the electronic properties of rutile TiO2 nanorods thus making it beneficial in UV photodetector application